How Welty doesn't crusade - Castilho, Maria Teresa (2013)
Eudora Welty firmly insists both in interviews and in her essay "Must the Novelist Crusade?" that her fiction is apolitical. As the writer states in One Writer's Beginnings, her stories are visions built not by particular political events or aims but, instead, by what she closely experienced and knew. With a thematic multiplicity concerning predominantly female characters and voices, and an undeniable complexity of meanings on the one hand, and a vision of the Southern difference on the other, what Welty really writes about is life, about human beings dominated by their emotions, their fantasies and their relationships. She writes about men and women (and above all women) as heirs of a Southern past or builders of a present that, in turn, conditions themselves and their history. And although the short story "Where is the Voice Coming From?", published in 1963, has been seen as the fictional text where Eudora Welty changed her attitude by breaking her silence on racial issues, it is important to understand that what she really did with it was to go deeper towards the human self and the human condition itself.